The design of political institutions: electoral competition and the choice of ballot access restrictions in the United States - Marcus Drometer; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2008)
Recent contributions to the political economics literature (Trebbi et al. 2007; Aghion et al. 2004) have challenged the view that political institutions are exogenous to the behaviour of agents in the political arena. We explicitly address the potential endogeneity of institutions by examining the link between the degree of electoral competition and the design of ballot access restrictions in the United States. Exploiting exogenous variation in electoral competition at the state level induced by the federal Voting Rights Act of 1965, our main finding is that restrictions to the entry of minor party and independent candidates have been systematically adjusted to changing degrees of electoral competition.
Keywords: D72; D78; 330; Political institutions; electoral competition; ballot access; Wahlrecht; Public Choice; Wahlkampf; USA